The impact of European design policies and their implications on the development of a framework to support future Brazilian design policies - Torres Do Patrocinio, Gabriel Henrique (Cranfield University, 2013)
About the theme: Public design policies can be explained as sets of principles established by a government intending to apply design into leveraging social, economical, industrial, and regional development. Design policy is an emerging theme in the field of design, and one that has been raising concerns from governments globally. Two aspects drive this interest: the extraordinary growth rates of the creative industries in the past decades; and the ability of Design to be a link between technology, creativity and the user, being a potential unique tool to help innovate and foster economic growth. About the research: The research was proposed responding an observed demand of governments in emerging countries to structure policies to use design to promote industrial and social development. It was structured to analyse current national and regional Design Policies within the framework of common aspects, effective practices and trends; external factors influencing their implementation; general causes of failures; assessment methods; and the influence of coexisting design definitions and trends. The focus is on Brazil, whose government is funding the research, the European Union, and the United Kingdom. In this context the research aims to generate a rationale for planning and assessment of Design Policies based on a review of current effective practices and identified future trends relevant to emerging markets. The main objective of the research is the identification and analysis of the constituent elements, driving forces, impacting factors, expected consequences, assessment methodologies and common failures of design policies. The intended goal is to respond to a demand for new knowledge, data, and tools that could contribute to reduce the current level of uncertainty regarding design policies. Methodology: To acknowledge the established objectives and goal, a comprehensive review of literature was initially carried out, including many reports and other documents from governments and from the EU. Emerging issues from the review informed a two-stage study developed in Brazil. For the first stage, in 2011, thirteen stakeholders were interviewed, from key active governmental programmes and departments. The choice of programmes and departments was validated by questions from the interview itself. The second stage, in 2012, focused on the only currently active design support programme aimed at SMEs in Brazil. During this phase, it was collected archival data and three interviews conducted. Collected data was analysed using descriptive statistic tools. The findings were then filtered using documents and archival data about European effective practices to inform the discussion and recommendations, and further used to generate a modelling framework for design policies. Contribution: The research contribution can be acknowledged in four different levels of outcomes: a comprehensive review of literature (1), combining an assortment of very significant documents and discussing their connections and specific contributions to the field; the application of an interview and archive based case study (2) about design policies in Brazil, corroborating Case Studies as a leading research tool for the area; a discussion on the impacting factors and effective practices of design policies (3); and finally the conceptual model and framework named respectively Compass Model and Create DP (4) that set together a framework intended to reduce levels of uncertainty in planning design policies.
Keywords: Design Policy; Design and Development; Innovation; Creative Economy; Public Policies; SMEs.